Migration and stereotypes in performance and culture - Meerzon, Yana; Dean, David; McNeil, Daniel (Contemporary performance interactions., 2020)
This book is an interdisciplinary collection of essays that delves beneath the media headlines about the "migration crisis", Brexit, Trump and similar events and spectacles that have been linked to the intensification and proliferation of stereotypes about migrants since 2015. Topics include the representations of migration and stereotypes in citizenship ceremonies and culinary traditions, law and literature, and public history and performance. Bringing together academics in the arts, humanities and social sciences, as well as artists and theatre practitioners, the collection equips readers with new methodologies, keywords and collaborative research tools to support critical inquiry and public-facing research in fields such as Theatre and Performance Studies, Cultural and Migration Studies, and Applied Theatre and History.